2014
DOI: 10.1161/hypertensionaha.114.03958
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Nocturnal Hypertension in Type 2 Diabetes Mellitus

Abstract: During the past decades, several studies in different populations have suggested that nighttime blood pressure (BP) is a stronger predictor of cardiovascular (CV) events than daytime BP. [1][2][3][4][5] Indeed, a recent meta-analysis concluded that nighttime BP is superior to daytime BP in predicting CV events and total mortality in both patients and general populations. 6 Consequently, treatment strategies to target nighttime BP have come into focus.Bedtime administration (BA) of different classes of antihype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 39 publications
0
17
0
6
Order By: Relevance
“…Compelling evidence is now available, showing that nocturnal BP is superior to daytime BP in predicting outcomes [7]. Subsequent www.cardiologyjournal.org studies in different populations and hypertensive patients corroborated the fact that a diminished nocturnal fall in BP was associated with poor CV outcomes and superior to daytime BP in predicting CV events and total mortality [12]. It was found that for every increase of 10 mm Hg in mean SBP at night, the risk of death increased by 21% [7].…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Compelling evidence is now available, showing that nocturnal BP is superior to daytime BP in predicting outcomes [7]. Subsequent www.cardiologyjournal.org studies in different populations and hypertensive patients corroborated the fact that a diminished nocturnal fall in BP was associated with poor CV outcomes and superior to daytime BP in predicting CV events and total mortality [12]. It was found that for every increase of 10 mm Hg in mean SBP at night, the risk of death increased by 21% [7].…”
Section: Discussionmentioning
confidence: 96%
“…Hermida et al [13] found that each 5-mm Hg decrease in mean sleep-time SBP was associated with a 14% reduction in the risk for CV events during follow-up (p < 0.001) among patients with chronic kidney disease and hypertension. Rossen et al [12] found levels of C-reactive protein were significantly lower with bedtime administration among patients with type 2 diabetes mellitus and nocturnal hypertension (p = 0.017), which may indicate an effect on low-grade inflammation.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations